Antenatal Depression as a Risk Factor of Stunting - Muhammad Akbar Nugraha; Budi Anna Keliat (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2020)
The incidence of stunting is one of the nutritional problems experienced by the world today. Depression during pregnancy is a neglected public health problem with broad effects on maternal and child health. The purpose of writing this article is to systematically identify description and relationship between antenatal depression and stunting in children. Systematic Review method is used for article search. Articles were identified from 2010-2020 by searching literature with the keywords